SYNTHESIS OF MCM-41 AS SUPPORT OF IRON AND COBALT CATALYST FOR FISCHER-TROPSCH REACTION - SEPTIAN FAUZI (NIM : 20514033), INDRA
Silica has long been used as a support to maximize surface area of catalyst and optimize the product in a heterogeneous catalysis process. The MCM-41 type is used as catalyst support due to its high surface area and thermal stability. The morphology of MCM-41 may change when different synthesis conditions is applied. The aim of this study is to investigate the effect of aging temperature of MCM-41 on its performance on Fischer-Tropsch reaction. In this study MCM-41 synthesis was performed by using Stöber sol-gel method at room temperature using TEOS as silica source and CTAB as structure directing agent. TEOS hydrolysis is carried out using ammonia solution in water. Synthesis was performed at varying pH and aging temperature to see the effect of synthesis condition. Fe-Ce and Co-Ce species deposition were carried out via incipient wetness impregnation using nitrate salt solution in water. FTIR Spectrum indicates silica formation. Diffractogram of silica synthesized at pH of 11 shows peaks at 2? of 2.64, 4.42 and 5.06 ° which are the typical peak of MCM-41. The morphology of silica synthesized at pH of 9 and 10 can not be observed in SEM images, whereas silica synthesized at pH of 11 has particle sizes in the range of 0.45-0.5 ?m with elliptical particles. Silica analysis using PSA showed an agglomerated silica. The presence of MCM-41 hexagonal mesoporous arrangement can be seen in TEM image of silica synthesized at pH of 11, whereas the TEM image of silica synthesized at pH of 9 and 10 do not show any regularity in the pores formed. Increasing silica surface area resulted in an increase in pH of synthesis. The highest surface area of 808 m2/g is owned by MCM-41 which is aged at room temperature. Type IV isotherm pattern is owned by MCM-41 which indicates that the pore size is in mesoporous category (2-5 nm). The largest average mesopore size is owned by MCM-41 aged at temperature of 120 ° C, which is 2.85 nm. The catalyst activity of preactivated catalyst Fe(NO3)3-Ce(NO3)3/MCM-41 and Co(NO3)2-Ce(NO3)3/MCM-41 was tested in Fischer-Tropsch reaction using micro fixed-bed reactor at atmospheric pressure, temperature of 350 ° C for iron catalyst and at temperature of 200 ° C for cobalt catalyst. The H2/CO ratio is 2 with flow rate of 5 mL/min. Previously the preactivated catalyst was activated by in situ reduction using H2 gas with flow rate of 8 mL/min at atmospheric pressure and temperature of 400 ° C for iron catalyst and temperature of 350 ° C for cobalt catalyst. Products of FT reaction using iron and cobalt catalysts were analyzed using GC. The activity of cobalt catalyst decreases at higher temperature. Selectivity of cobalt catalyst towards C4+ is reduced at higher temperature. The activity and selectivity of cobalt catalyst towards C4+ products is strongly related to the size of pore formed on the support. The greater the mean mesoporous size of MCM-41, the higher the activity and selectivity of catalyst towards C4+. Meanwhile, the product of FT reaction using iron catalyst showed only one peak on its chromatogram. The peak is similar to that of syn-gas and ethylene chromatograms. The result of H-NMR analysis on the product of FT reaction using iron catalyst only showed hydrogen signal of water molecule and H2 molecule, so it can be concluded that iron catalyst in this study is not active for Fischer-Tropsch reaction.